Langzeitergebnisse nach roboterassistierter Adenomenukleation = Long-term results after robot-assisted adenoma enucleation - Häcker, Axel; Thüroff, Joachim W. (Genome, 2016)
For selected patients with large-volume prostates, open simple prostatectomy is an effective and durable treatment option. Robot-assisted simple prostatectomy potentially reduces intraoperative blood loss, transfusion rates, length of hospital stay, and complications, but has longer operative times. In all, 16 series with level 3 evidence have been published and demonstrated its safety and efficacy. Long-term data are lacking and comparative outcome studies are needed to establish its benefits compared to open, simple prostatectomy and transurethral laser enucleation techniques.
Gesehen am 22.05.2019